iNKT Cell Emigration out of the Lung Vasculature Requires Neutrophils and Monocyte-Derived Dendritic Cells in Inflammation - Ajitha Thanabalasuriar; Arpan S. Neupane; Jing Wang; Matthew F. Krummel; Paul Kubes (Cell Reports, 2016)
iNKT cells are a subset of innate T cells that recognize glycolipids presented on CD1d molecules and protect against bacterial infections, including S. pneumoniae. Using lung intravital imaging, we examined the behavior and mechanism of pulmonary iNKT cell activation in response to the specific iNKT cell ligand α-galactosylceramide or S. pneumoniae infection. In untreated mice, the major fraction of iNKT cells resided in the vasculature, but a small critical population resided in the extravascular space in proximity to monocyte-derived DCs. Administration of either α-GalCer or S. pneumoniae induced CD1d-dependent rapid recruitment of neutrophils out of the vasculature. The neutrophils guided iNKT cells from the lung vasculature via CCL17. Depletion of monocyte-derived DCs abrogated both the neutrophil and subsequent iNKT cell extravasation. Moreover, impairing iNKT cell recruitment by blocking CCL17 increased susceptibility to S. pneumoniae infection, suggesting a critical role for the influx of iNKT cells in host defense.